Flame synthesis of carbon nanotubes on glass fibre fabrics and their enhancement in electrical and thermal properties of glass fibre/epoxy composites. (1st October 2020) - Zhao, Guixiang; Liu, Hong-Yuan; Du, Xusheng; Zhou, Helezi; Pan, Zhu; Mai, Yiu-Wing; Jia, Yuan-Yuan; Yan, Wenyi
Abstract: A novel one-step flame synthesis method was used to coat carbon nanotubes (CNTs) onto plain weave S-glass fibre (GF) fabrics. Nickel chloride, as a catalyst, was applied on the GF fabrics, and CNTs were formed in an ethanol flame. Results showed that different carbon materials were synthesised, and they were sensitive to the flame synthesis parameters. Short CNTs (shorter than 0.5 μm) were dominant with a low catalyst concentration of 0.2 mol/L, and long CNTs (lengths of 1.2–2.0 μm) started to appear when the catalyst was increased to 0.4 and 0.6 mol/L. With even higher catalyst concentration at 0.8 and 1.0 mol/L, most of the CNTs were embedded in a thick layer of carbon soot. In addition, the thermal and electrical conductivities of GF/epoxy and multi-scale CNT-GF/epoxy composites were measured. Compared to GF/epoxy composite, a more than 40% increase of thermal conductivity and 10 orders of magnitude decrease of electrical resistance were achieved in these multi-scale CNT-GF/epoxy composites. Highlights: CNTs were successfully synthesised in an ethanol flame and coated onto glass fibres. Catalyst concentration influenced significantly the composition of the synthesised carbon materials. The multi-scale CNTs-glass fibre composite laminates exhibited enhanced thermal and electrical conductivities.